The Effect of Upper Eyelid Blepharoplasty on Corneal Tomography and Epithelial Profile - Carreira P; Loureiro T; Carreira AR; Gouveia-Moraes F; Cardoso A; Sampaio A; Campos P; Rodrigues-Barros S; Machado I; Campos N (Clinical Ophthalmology, 2023)
Pedro Carreira, Tomás Loureiro, Ana Rita Carreira, Filipe Gouveia-Moraes, Ana Cardoso, Audrey Sampaio, Paul Campos, Sandra Rodrigues-Barros, Ines Machado, Nuno Campos Centro de Responsabilidade Integrada de Oftalmologia, Hospital Garcia de Orta, Almada, PortugalCorrespondence: Tomás Loureiro, Centro de Responsabilidade Integrada de Oftalmologia, Hospital Garcia de Orta, E.P.E, Av. Torrado da Silva, Almada, 2805-267, Portugal, Email loureiro.tomas@gmail.comIntroduction: Upper tarsal mechanical forces influence corneal epithelial thickness profile, which could modulate corneal astigmatism. Upper eyelid blepharoplasty reduces upper tarsal strength and may have an impact on ocular surface. The aim of this study is to evaluate the effect of upper eyelid blepharoplasty on corneal epithelial thickness profile, astigmatism and aberrations.Methods: Patients with dermatochalasis underwent bilateral upper eyelid blepharoplasty. Anterior segment optical coherence tomography (AS-OCT) (Zeiss Cirrus 5000 HD-OCT) and Pentacam (Oculus, Wetzlar Germany) were performed before surgery and in the 8th postoperative week. Corneal epithelial thickness, keratometry, aberrations and asphericity were considered for statistical purposes. Only right eyes were considered. A p-value lower than 0.05 was considered significant.Results: Thirty eyes of 30 patients were included. The degree of astigmatism did not change after surgery (0.95D vs 0.83D, p=0.23). The difference between preoperative and postoperative steepest axis was 3.1° (p=0.04) with a tendency to change toward the vertical meridian. Mean epithelial thickness was higher in the inferior region both pre- and postoperatively and did not change. ET in the superior octant was lower (42 μm vs 45 μm, p< 0.01) and the difference between inferior and superior octants (I-S) was higher (7 μm vs 3 μm, p< 0.001) before surgery. There were no statistically significant changes in corneal aberrations (p=0.52) and asphericity (p=0.41) after surgery.Conclusion: Our results support that upper tarsus pressure influences epithelial thickness profile and, consequently, the corneal steepest keratometry. These results lead us to postulate that upper eyelid blepharoplasty may influence biometric and keratometric measurements.Keywords: Blepharoplasty, Epithelial Thickness, Corneal Tomography, Anterior-Segment Optical Coherence Tomography